Hydrogen generation from CaCl2 and MgCl2 using the chlor-alkali process - Damarseckin, Serdal; Karakilcik, Mehmet (Springer, 2025)
Hydrogen is considered a clean energy carrier with high potential for sustainable energy systems, yet the majority of industrial hydrogen production relies on non-renewable resources such as natural gas, petroleum, and coal, contributing to environmental pollution and greenhouse gas emissions. To address these challenges, alternative electrolytes for hydrogen production in chlor-alkali reactors have been proposed, but comprehensive studies comparing their energetic and sustainable performance are limited. In this study, the production of hydrogen via the chlor-alkali process using CaCl2 and MgCl2 salts is experimentally investigated under cell voltages of 5, 7.5, and 10 V, with inlet temperatures of 20 and 45 degrees C. The experiments were conducted in a membrane-based chlor-alkali reactor equipped with carbon rod electrodes and a Nafion 212 membrane to separate the anode and cathode compartments. Hydrogen production was quantified by the volumetric displacement method, and the corresponding energy efficiencies were calculated based on the applied electrical input. According to the experimental results, the reactor produces 30 mL of hydrogen using CaCl2 and MgCl2 at 20 degrees C and 5 V in durations of 19 and 27.42 min, respectively. At 10 V, the reactor generates the same amount of hydrogen much faster, taking only 2.2 min with CaCl2 and 10.05 min with MgCl2. The highest energy efficiency for CaCl2 is achieved at 45 degrees C and 7.5 V, with a value of 12.90%, while for MgCl2, it is observed under the same conditions, with a value of 5.10%. CaCl2 consistently outperforms MgCl2 in hydrogen production across varying temperatures and voltages. This study aims to provide a clear comparison of these alternative salts, offering insights into optimizing energy efficiency and sustainability in hydrogen production processes.
Keywords: Energy efficiency; CaCl2 and MgCl2 performance; Electrochemical processes; Voltage optimization; Temperature effect; Hydrogen yield